How have district-based house price earnings ratios evolved in England and Wales? - David Paul Gray (Journal of Risk and Financial Management, 2022)
The central aim of this paper is to provide a baseline framework for describing the evolution of an affordability indicator at a district level, before and after the financial crisis of 2008. From the mid-1990s to 2019 house price-earnings ratio for England and Wales appear to have ratcheted-up, with the growth rate more rapid just before and a temporary decline just after the crisis. This masks a significant variation in evolutionary profiles. Following Turok and Mykhnenko in 2007 who set about exploring population trends in European cities, districts are classified into groups. Matching each district against ten stylised profiles, rather than cycles, persistent trends and single turning point paths in ratios are the norm. An asset-price model projects that finance will favour those bright futures so that spatial-sorting of those with high human capital leads to some districts benefitting from lending criteria out of line with others.
Keywords: 650; an asset-price model; house price-earnings ratios; Jonckheere-Terpstra test; Kendall’ s W; local authority districts